A novel role for the proteasomal chaperone PSMD9 and hnRNPA1 in enhancing IκBα degradation and NF‐κB activation – functional relevance of predicted PDZ domain–motif interaction. (30th April 2014) - Sahu, Indrajit; Sangith, Nikhil; Ramteke, Manoj; Gadre, Rucha; Venkatraman, Prasanna
<x xml:space="preserve">Abstract</x> PSMD9 is a PDZ domain containing chaperone of proteasome assembly. Based on the ability of PDZ‐like domains to recognize C‐terminal residues in their interactors, we recently predicted and identified heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) as one of the novel interacting partners of PSMD9. Contingent on the reported role of hnRNPA1 in nuclear factor κB (NF‐κB) activation, we tested the role of human PSMD9 and hnRNPA1 in NF‐κB signaling. We demonstrated in human embryonic kidney 293 cells that PSMD9 influences both basal and tumor necrosis factor α (TNF‐α) mediated NF‐κB activation through inhibitor of nuclear factor κB α (IκBα) proteasomal degradation. PSMD9 mediates IκBα degradation through a specific domain–motif interaction involving its PDZ domain and a short linear sequence motif in the C‐terminus of hnRNPA1. Point mutations in the PDZ domain or deletion of C‐terminal residues in hnRNPA1 disrupt interaction between the two proteins which has a direct influence on NF‐κB activity. hnRNPA1 interacts with IκBα directly, whereas PSMD9 interacts only through hnRNPA1. Furthermore, hnRNPA1 shows increased association with the proteasome upon TNF‐α treatment which has no such effect in the absence of PSMD9. On the other hand endogenous and trans‐expressed PSMD9 are found associated with the proteasome complex. This association is unaffected by PDZ mutations or TNF‐α treatment. Collectively, these interactions between IκBα, hnRNPA1 and proteasome bound PSMD9 illustrate a potential mechanism by which ubiquitinated IκBα is recruited on the proteasome for degradation. In this process, hnRNPA1 may act as a shuttle receptor and PSMD9 as a subunit acceptor. The interaction sites of PSMD9 and hnRNPA1 may emerge as a vulnerable drug target in cancer cells which require consistent NF‐κB activity for survival.